2015
DOI: 10.1186/s13075-015-0836-6
|View full text |Cite
|
Sign up to set email alerts
|

Higher education is associated with a better rheumatoid arthritis outcome concerning for pain and function but not disease activity: results from the EIRA cohort and Swedish rheumatology register

Abstract: IntroductionWhether low socioeconomic status (SES) is associated with worse rheumatoid arthritis (RA) outcomes in countries with general tax-financed healthcare systems (such as Sweden) remains to be elucidated. Our aim was to investigate the influence of educational background (achieving university/college degree (high) or not (low)) on the outcomes of early RA, in terms of disease activity (DAS28), pain (VAS-pain), and functional impairment (HAQ).MethodsWe evaluated DMARD-naïve RA patients recruited in the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 23 publications
3
34
1
Order By: Relevance
“…The link between higher education and lower functional disability and higher rates of employment is interesting. These associations are well‐established in RA , but less so in SpA. Our results suggest that the relationship between comorbidities and the outcomes is independent of the effect of education, and that a higher education is associated with lower functional disability and a higher rate of employment.…”
Section: Discussionmentioning
confidence: 52%
“…The link between higher education and lower functional disability and higher rates of employment is interesting. These associations are well‐established in RA , but less so in SpA. Our results suggest that the relationship between comorbidities and the outcomes is independent of the effect of education, and that a higher education is associated with lower functional disability and a higher rate of employment.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, the present study concludes educational level of the patients as one of the influencing factors of treatment outcome. Contrary to this finding, a Swedish cohort study has reported that educational background does not influence DAS28‐based outcomes in RA patients, although it had been demonstrated that patients with higher education level experienced less pain and reduced functional disability . Although family income has direct relationship with education, these confounding factors did not influence the treatment protocol.…”
Section: Discussionmentioning
confidence: 73%
“…It is important to note that in countries with generally easily accessible healthcare systems, educational background does not directly impact disease activity but patients with a higher educational level may have slightly less pain and less functional disability. This was explored in a study conducted in Sweden (22).…”
Section: Discussionmentioning
confidence: 99%